2019
DOI: 10.1242/dev.180422
|View full text |Cite
|
Sign up to set email alerts
|

Motor pools organization depends on the combined function of N-cadherin and type II cadherins

Abstract: Type I and type II classical cadherins constitute a family of cell adhesion molecules expressed in complex combinatorial profiles in the nervous system, suggesting that a cadherin code implements specific adhesive recognition events that control the development of neural circuits. In the spinal cord, classical cadherins define at a molecular level the positional organization of motor neuron subtypes into discrete nuclear structures termed motor pools. However, the roles and contributions of different members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…We next generated mice deficient for each Cdh locus by intercrossing to show that these mice are virtually viable and fertile with no fatal phenotype, which is in line with previous series of reports 31,[36][37][38][39] . Using western blotting in tissues derived from these single KO mice, we also confirmed that manipulated alleles for the three type II Cdh genes are all protein null (Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…We next generated mice deficient for each Cdh locus by intercrossing to show that these mice are virtually viable and fertile with no fatal phenotype, which is in line with previous series of reports 31,[36][37][38][39] . Using western blotting in tissues derived from these single KO mice, we also confirmed that manipulated alleles for the three type II Cdh genes are all protein null (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Gain of function studies for Cdh subclasses in vivo have accordingly revealed that differential and dynamic Cdh expression switches are crucial in neurulation 29 , 30 , compartmentalization 31 , neural crest emigration 32 , and precise positioning of spinal motor neurons 33 during early development. However, loss of function studies using mouse indicated that, in striking contrast with the early embryonic lethal phenotype for type I Cdh1 (=E-cadherin)-/- 34 or Cdh2 (=N-cadherin)-/- 35 mice, most type II Cdh single knockout mice and some combinatorial mutants show few embryonic phenotypes despite the considerable levels of early expression 31 , 36 39 . This has often been ascribed to “molecular and/or functional redundancy” of Cdhs, yet no direct evidence for their necessity in early embryogenesis is provided thus far.…”
Section: Introductionmentioning
confidence: 99%
“…We find that several cadherins, including cdh2 and cdh11 , are expressed by all subnuclei, highlighting them as prime candidates to drive baseline levels of adhesion via homophilic interactions. Recent work raises the possibility that heterophilic interactions between type II cadherins belonging to specificity groups, such as cdh8 (expressed to varying degrees by IR/MR and SR) and cdh11 (expressed by all ocular motor neurons), could also participate, in collaboration with cdh2 ( Brasch et al, 2018 ; Dewitz et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the molecular and cellular processes which give rise to subnuclear topography remain unknown. The positioning of some groups of motor neurons has been shown to be regulated by members of the classical cadherin superfamily of cell adhesion molecules, which include type I and type II cadherins ( Price et al, 2002 ; Demireva et al, 2011 ; Astick et al, 2014 ; Dewitz et al, 2018 ; Dewitz et al, 2019 ). Differential expression of type II cadherins, which participate in homophilic as well as heterophilic interactions ( Patel et al, 2006 ), drives the segregation and coalescence of somatomotor and branchiomotor neurons into discrete cranial motor nuclei in the hindbrain ( Astick et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This gave rise to the hypothesis of functional redundancy and the systematic analysis of double and triple knock-outs for closely related family members. [59,60,62] For example, a triple knock-out of Cadherins 6, 9, and 10 causes a highly specific defect in the wiring of the retina, [60] but no defect in the sorting of motor pools in the spinal cord. [62] The triple-knock-out mice are viable and fertile.…”
Section: Phenotypic Penetrance and Genetic Sensitization Are Measuresmentioning
confidence: 99%